2019
DOI: 10.1158/1541-7786.mcr-18-0990
|View full text |Cite
|
Sign up to set email alerts
|

Serine Threonine Kinase 17A Maintains the Epithelial State in Colorectal Cancer Cells

Abstract: Serine Threonine Kinase 17A (STK17A) is a ubiquitously expressed kinase originally identified as a regulator of apoptosis; however, whether it functionally contributes to colorectal cancer (CRC) has not been established. Here, we have analyzed STK17A in CRC and demonstrate decreased expression of STK17A in primary tumors which is further reduced in metastatic lesions, indicating a potential role in regulating the metastatic cascade. Interestingly, changes in STK17A expression did not modify proliferation, apop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Enrichment GO analysis also suggested that miR-106a and miR-106b were both mostly correlated with the vital cell components including nucleus, nucleoplasm and nucleolus, which have been demonstrated to be associated with the proliferation and invasion of CRC [42]. For MF, the targets of miR-106a and miR-106b were mainly linked with the binding function and enzyme activity, which has also been proved to be involved in the development and classification of CRC [43,44]. What's more, the KEGG pathway enrichment analysis revealed that some important pathways associated with miR-106a and miR-106b might take part in the pathogenesis of CRC according to literature exploration.…”
Section: Fig 4 Sensitivity Analysis Results In the Meta-analysis Formentioning
confidence: 99%
“…Enrichment GO analysis also suggested that miR-106a and miR-106b were both mostly correlated with the vital cell components including nucleus, nucleoplasm and nucleolus, which have been demonstrated to be associated with the proliferation and invasion of CRC [42]. For MF, the targets of miR-106a and miR-106b were mainly linked with the binding function and enzyme activity, which has also been proved to be involved in the development and classification of CRC [43,44]. What's more, the KEGG pathway enrichment analysis revealed that some important pathways associated with miR-106a and miR-106b might take part in the pathogenesis of CRC according to literature exploration.…”
Section: Fig 4 Sensitivity Analysis Results In the Meta-analysis Formentioning
confidence: 99%
“…TCGA data, however, reflected the increased expression of both IL32 and STK17A in STADs compared with non-malignant pairs at gene level, and the potential association of their expression with STAD prognosis. It should be noted that the expression patterns and prognostic association of STK17A in STADs were in contrast to other tumors 36 .…”
Section: Discussionmentioning
confidence: 87%
“…IL32 has been reported to relate with carcinogenesis, metastasis, angiogenesis, and regulation of the antitumor immune response in various tumors 35 . STK17A is a ubiquitously expressed kinase, which was reported to regulate apoptosis, epithelial phenotypes, etc., and showed suppression on tumor progression and invasion in several other tumors 36 . Neither IL32 nor STK17A showed apparent expression difference at gene level but both showed SRCC-specific isoforms, for which SGS short-read quantification also supported the substantial increase of expression in SRCCs at the isoform level (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Enrichment GO analysis also suggested that miR-106a and miR-106b were both mostly correlated with the vital cell components including nucleus, nucleoplasm and nucleolus, which have been demonstrated to be associated with the proliferation and invasion of CRC [41]. For MF, the targets of miR-106a and miR-106b were mainly linked with the binding function and enzyme activity, which has also been proved to be involved in the development and classification of CRC [42,43].…”
Section: Function Exploration Of Mir-106 Family In Crcmentioning
confidence: 99%